2016
DOI: 10.1002/jbm.a.35803
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐osteoclastic in vitro effect of Polyethylene‐like nanoparticles: Involvement in the pathogenesis of implant aseptic loosening

Abstract: Polyethylene micro‐sized wear particles released from orthopedic implants promote inflammation and osteolysis; however, less is known about the bioactivity of polyethylene nanosized wear particles released from the last generation of polymer‐bearing surfaces. We aim to assess the internalization of fluorescent polyethylene‐like nanoparticles by both human macrophages and osteoclasts and also, to determine their effects in osteoclastogenesis in vitro. Human macrophages and osteoclasts were incubated with severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…These cytokines directly recruit and activate osteoclasts to resorb adjacent bone. 13,83 Dean et al 24 found that transforming growth factor (TGF)-β production decreased while prostaglandin (PGE)-2 production increased when osteoblast-like cells were exposed to conventional ultra-high-molecular-weight polyethylene (UHMWPE) particles in vitro. This pro-inflammatory environment led to increased rates of osteolysis with a corresponding decrease in osteoblastic activity and extracellular matrix production.…”
Section: Pathogenesismentioning
confidence: 99%
“…These cytokines directly recruit and activate osteoclasts to resorb adjacent bone. 13,83 Dean et al 24 found that transforming growth factor (TGF)-β production decreased while prostaglandin (PGE)-2 production increased when osteoblast-like cells were exposed to conventional ultra-high-molecular-weight polyethylene (UHMWPE) particles in vitro. This pro-inflammatory environment led to increased rates of osteolysis with a corresponding decrease in osteoblastic activity and extracellular matrix production.…”
Section: Pathogenesismentioning
confidence: 99%
“…This study aimed to explore whether TMV viral nanoparticles could impact osteoclast differentiation as different nanoparticles were shown to modulate osteoclastogenesis. 11,12,[21][22][23][24][25] Gold nanoparticle (GNP) was one of the well-studied inorganic nanoparticles on osteoclastogenesis. [21][22][23] β-cyclodextrin (CD) conjugated GNPs carrying curcumin and alendronate functionalized GNPs inhibited RANKL-induced mouse bone marrowderived macrophages differentiation into tartrate-resistant acid phosphatase (TRAP)-positive multinuclear osteoclasts and the expression of osteoclastogenic genes c-Fos, Nfatc1, Trap, and Oscar in vitro and improved bone density of ovariectomized mice.…”
Section: Discussionmentioning
confidence: 99%
“…24 Polyethylene-like nanoparticles were readily internalized by human macrophages and osteoclasts and promoted osteoclastogenesis. 11 Ultra-high molecular weight polyethylene wear particles promoted inflammatory responses and osteoclastogenesis of Raw264.7 cells with elevated expression of osteoclast markers MMP-9, Calcr, and Ctsk. 25 These data showed that a variety of nanoparticles could change the course of osteoclast differentiation, which inspired the current study to investigate the impact of TMV VNPs on osteoclastogenesis in vitro and on bone injury healing in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in an in vitro pilot test, we harvested osteoclasts daily over a period of 12 days ( n = 1) and found that, at day 12, a high amount of hydroxyapatite was already degraded. We hypothesized that osteoclast activity might increase after addition of PLL/CS PEC-NPs and BDNF as shown by Brulefert et al for polyethylene nanoparticles [39]. Thus, changes between the groups might have not been measureable since in controls a high amount of the hydroxyapatite had been resorbed already.…”
Section: Discussionmentioning
confidence: 99%